Boosting ferroptosis via abplatin(iv) for treatment of platinum-resistant recurrent ovarian cancer. (June 2022) - Wang, Wenwen; Cai, Jing; Wen, Jiayi; Li, Xinyi; Yu, Yingjie; Zhang, Lingpu; Han, Qing; Wei, Zheng; Ma, Yujia; Ying, Feiquan; Xu, Xiaohan; Li, Wenhan; et al.
Abstract: Platinum resistance represents a huge difficulty in ovarian cancer treatment, resulting in disease recurrence and deaths in patients. However, platinum-resistant, recurrent diseases still lack fundamentally effective treatment. Herein, four platinum(IV) (Pt(IV)) prodrugs were developed from the most widely used cisplatin (CisPt) and oxaliplatin (OxaPt), which were subsequently loaded with human serum albumin (HSA) to form nanoparticles (NP1-NP4). We found that NP1, also named Abplatin (iv), showed the best anticancer activity in six ovarian cancer cell lines of various pathological types. Hence, Abplatin (iv) was further evaluated in terms of translational potential. We established patient-derived cells (PDCs) and patient-derived organoids (PDOs) and observed enhanced antitumor effects of Abplatin (iv) in these ex vivo models. Furthermore, in mice bearing orthotopic ovarian cancer, intraperitoneal administration of Abplatin (iv) resulted in targeted drug accumulation in tumors and decreased tumor burden more effectively than CisPt, without causing any detectable side effects. In addition, by analyzing single-cell transcriptome sequencing results, we found a phenotypic shift toward stem-like cells in ovarian cancers undergoing chemotherapy. Therefore, cancer stem cells (SKOV3–3rd) mimicking such persistent tumor cells in postchemotherapeutic residual lesions were established. Abplatin (iv) exhibited a significantly improved antitumor effect on SKOV3–3rd cells both in vitro and in vivo . Finally, RNA sequencing revealed that Abplatin (iv) worked by boosting cell ferroptosis compared with CisPt. Taken together, Abplatin (iv) exhibits low systemic toxicity and high anticancer activity. In particular, it shows robust efficacy against platinum-resistant ovarian cancer derived from patients, indicating its great clinical translation potential. Graphical Abstract: ga1 Highlights: Abplatin (iv), an albumin nanoparticle with Pt(IV) prodrugs, exhibits low systemic toxicity and high anti-cancer activity; Abplatin (iv) boosts cell ferroptosis to improved anti-tumor effect; Abplatin (iv) holds great clinical translation potential.